EDUCATIONAL VALUE THROUGH SEMIOTICS: ANALYZING SONG A MILLION DREAMS TO IAIN PAREPARE STUDENTS - Firmansyah JN, Muh; Aswad, Muhammad; Nursal, Muhammad Akbar; Sardi, Ahmed (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Darud Da'wah Wal Irsyad Pinrang, 2025)
This study aimed to explore how 8th-semester English Education (PBI) students at IAIN Parepare conducted a semiotic analysis of the song A Million Dreams, performed by Hugh Jackman and Michelle Williams, and to understand their perceptions of the educational values within the lyrics. Using a qualitative descriptive method, the research involved 30 randomly selected students as participants. Data were collected through interviews and voice recordings. The findings revealed that students identified various types of semiotic signs in the lyrics: one lyric represented an icon, six were categorized as indices, and three were recognized as symbols. Regarding educational values, students highlighted several moral lessons conveyed through the song. The values identified included religiousness (1 student), responsibility (6), hard work (13), friendliness (4), appreciation (1), creativity (11), love for reading (7), environmental awareness (2), peace (2), independence (4), curiosity (2), and discipline (2). These responses suggest that A Million Dreams contains a wide range of educational messages that resonate differently with each student, with hard work and creativity being the most frequently recognized. The study underscores the song’s effectiveness in communicating positive values through music and lyrical content.